A description of the coagulopathy characteristics in amniotic fluid embolism: a case report. (August 2022) - Oliver, C.; Freyer, J.; Murdoch, M.; De Lloyd, L.; Jenkins, P.V.; Collis, R.; Collins, P.W.
Highlights: Amniotic fluid embolism (AFE) coagulopathy features are incompletely understood. Clotting factors, thrombin generation, fibrinogen, and D-dimers were measured. Acute hypofibrinogenaemia, dysfibrinogenaemia and massive fibrinolysis were seen. Clotting factor levels remained haemostatic and thrombin generation was preserved. Treatment of hyperfibrinolysis and hypofibrinogenaemia may improve AFE outcome. Abstract: Amniotic fluid embolism is frequently associated with coagulopathy. However, the exact nature and evolution of the bleeding disorder is incompletely understood. We report a case of clinically diagnosed amniotic fluid embolism associated with major haemorrhage and coagulopathy. We measured sequential levels of all individual clotting factors, thrombin generation, fibrinogen, and D-dimer levels over the course of the event, beginning shortly after the patient's initial collapse and during the subsequent resuscitation, to identify the specific abnormalities of coagulation from stored blood samples. A better understanding of amniotic fluid embolism and the associated coagulopathy is an important area of research to inform targeted treatment of the coagulopathy and improve outcomes for patients.